DIFFERENCES AND SIMILARITIES OF PROBLEMS OF EDUCATION QUALITY AND DIGITALIZATION TECHNOLOGIES IN SECONDARY AND HIGHER SCHOOLS - Bizyuk , Valeriy Vasylovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article explores key challenges in education quality and the specifics of implementing digital technologies in secondary and higher education. A comparative analysis of shared and distinct aspects of digitalization in the learning process, student motivation, and management strategies across these two educational levels is conducted. International experiences of digitalization and their impact on educational policy are examined. The study concludes that a comprehensive approach is essential to ensuring education quality in the context of digital transformation.